Journeying Through Informing, Reforming and Transforming Teacher Education: Reflections on Curriculum Images - Qutoshi, Sadruddin Bahadur (Journal of Transformative Praxis, 2021)
This paper aims to address ‘how an auto/ethnographic muse explores informing, reforming and transforming states of teacher education and research practices.’ I critique informing and reforming states of teacher education in Pakistan for the limitations associated with these approaches rooted within the colonial system of education. Within these two approaches to education, I share the experiences of teaching, learning, research practices, and beliefs, which could not address a broader view of teacher education. To address the research problem, I applied an unconventional approach to research by using auto/ethnography as a methodological referent within a multi-paradigmatic research design space. In so doing, I used the paradigms of interpretivism, criticalism, postmodernism, and integralism as data referents, which enabled me to capture the lived experiences of my professional lifeworld at different stages. Moreover, I used critical reflections on the experiences as a teacher, teacher educator, and researcher as epistemic techniques to explore, explain and construct meaning out of the perceptions, beliefs, and practices. Perhaps, engaging autobiographically as an approach to knowing deep-seated views and practices and critically reflecting on the embodied values of practices open new ways of being and becoming a transformative learner(s). This paper invites readers to reflect critically on their own deep-seated practices by using such unconventional approaches to research that would enable them to experience a paradigm shift in their thinking, believing, viewing, and doing. I believe that in doing so, practitioners as researchers, with their own embodied values of practice in their professional lives, can transform self/others by creating their own living-educational-theories.